Development of Green Open Space Policy in The Order to Realize A Sustainable City in Malang - Switsa Cellindita; Ach Apriyanto Romadhan; Ali Roziqin (Universitas Muhammadiyah Gorontalo, 2021)
The current massive industrial development in urban areas that is not balanced with reforestation practices will have an impact on the environment such as air pollution, hot environmental conditions, flooding, and the lack of adequate Green Open Space. Therefore, good urban spatial planning is needed through the development of green open space in urban areas to maintain or facilitate urban settlements and reforestation practices for the future urban sustainability agenda so that there is a balance in terms of the economic, social, and natural environment as a form of a sustainable city. In analyzing the problem of this research using the literature study method by analyzing the results and information from previous studies. The result of the research is that the development of green open space in Malang City has not been fully managed properly, this is in accordance with the percentage of public green open space in Malang City which is only 1.362.32 Ha or 12.38% which the results of this percentage are still far from the minimum proportion of public green open space, which is 20% of the area of Malang City. As less than the maximum development of green open space, it will also have an impact on a sustainable city that runs less than optimally.